The Effect of High-Power Lasers on Root Canal Disinfection: A Systematic Review: High-Power Lasers and Root Canal Disinfection - Asnaashari, Mohammad; Sadeghian, Ali; Hazrati, Parham (Journal of Lasers in Medical Sciences, 2022)
Introduction: In root canal therapy, the cleaning and shaping of canals are routinely applied by clinicians in order to remove microorganisms. Eradicating bacteria from the root canal system plays a crucial role in long-term success; however, it is not always easy to disinfect root canals properly because of their complicated anatomy and bacterial load. Achieving an optimally disinfected root canal environment requires adjunctive antibacterial therapeutic methods. High-power laser utilization as an adjunctive strategy to conventional treatment is a relatively new approach that helps clinicians. Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Online databases, namely Web of Science, PubMed/MEDLINE, Scopus, and Cochrane Library, were searched electronically regarding lasers and endodontic treatments. Appropriate studies were included according to the inclusion/exclusion criteria. Results: Among 504 obtained studies by search, 48 were considered for a detailed analysis. Ten articles performed in vivo evaluation, nine assessed the effect of lasers on artificial models, and 29 conducted ex vivo experiments on extracted teeth. When the diode laser, the most frequently used laser, was utilized as an adjunct therapy after NaOCl irrigation, it killed more bacteria than conventional irrigation with NaOCl. Laser-activated irrigation (LAI) with the Er, Cr: YSGG laser, and NaOCl disinfects the root canal effectively. Also, photon-induced photoacoustic streaming (PIPS) with Er: YAG and NaOCl exhibited a high bactericidal effect and deep tubular penetration. Conclusion: High-power laser utilization, considering proper case selection and method, can assist in root canal treatment of infected teeth.